2010
DOI: 10.3109/10641955.2010.506235
|View full text |Cite
|
Sign up to set email alerts
|

Acute and ChronicChlamydia pneumoniaeInfection in Pregnancy Complicated with Preeclampsia

Abstract: Chronic Cp infection is not more common in women whose pregnancy is complicated with PE as compared to pregnant women without PE. Therefore, no association between Cp infection and PE can be established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 13 publications
1
3
0
2
Order By: Relevance
“…The null relationships between C. pneumoniae , HSV-2, CMV, and preeclampsia found in our study are consistent with other longitudinal, 24 case-control, 14 and metaanalysis 25 studies, although literature is conflicting. 8;9;13;16;23 The reason for these discrepancies is not entirely clear, but it is possible that bacterial and viral infections are not universally associated with preeclampsia.…”
Section: Resultssupporting
confidence: 90%
“…The null relationships between C. pneumoniae , HSV-2, CMV, and preeclampsia found in our study are consistent with other longitudinal, 24 case-control, 14 and metaanalysis 25 studies, although literature is conflicting. 8;9;13;16;23 The reason for these discrepancies is not entirely clear, but it is possible that bacterial and viral infections are not universally associated with preeclampsia.…”
Section: Resultssupporting
confidence: 90%
“…20 Raynor et al and Chrisoulidou et al also found no difference in the rate of seropositivity between PE and normal pregnancy. 21,22 Others, however, found that C.pneumonie may be a coprecipitating factor and its role in development of PE needs to be supported by further studies. Xie et al, examined C.pneumoniae IgG by ELISA and C.pneumoniae genomic DNA loads by real-time PCR in a case-control study on women with PE, normal term pregnancies and non-pregnant controls.…”
Section: Discussionmentioning
confidence: 95%
“…17 However, other studies showed conflicting results. [20][21][22] Xie F et al, recommended need for further studies. 23 Mosbah et al, studied the effect of Helicobacter pylori, Chlamydiae pneumoniae and trachomatis as probable etiological agents of preeclampsia and recommended further studies.…”
mentioning
confidence: 99%
“…The first phase refers to hypoperfusion of the placenta, impaired trophoblast invasion, and inadequate remodeling of the uterine spiral arteries, leading in reduced blood supply to the fetus as the spiral arteries remain narrow . During the second phase, metabolic, inflammatory, and thrombotic responses are observed that cause endothelium dysfunction, proteinouria, and multiorgan damage . Placental hypoxia leads to oxidative stress and release into the maternal circulation of trophoblast debris, as well as soluble factors, such as the angiogenic markers soluble endoglin and fms‐like tyrosine kinase 1 (sFlt‐1) .…”
Section: The Pathogenesis Of Pementioning
confidence: 99%